2021
DOI: 10.1108/lodj-02-2021-0092
|View full text |Cite
|
Sign up to set email alerts
|

The resilient effects of transformational leadership on well-being: examining the moderating effects of anxiety during the COVID-19 crisis

Abstract: PurposeAlthough important for organizational performance, much is still unknown about the relationship between employee well-being and transformational leadership. The authors answer calls to consider the relationship (1) in an extreme context (i.e. coronavirus pandemic), (2) at the dimension level and (3) differences that exist depending on the employee's gender.Design/methodology/approachThe authors employed a two-wave study with data collected from 212 working individuals. Respondents reported their level o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 32 publications
1
22
0
Order By: Relevance
“…Regarding the impact of management practice, McCombs and Williams (2021) found that in an epidemic situation, shorter-term performance expectations do not impair employees' wellbeing. However, this can only be achieved if management communication inspires trust, is caring and sufficiently detailed in terms of tasks (Shipman et al, 2021).…”
Section: Organizational Citizenship Behavior and Remote Workmentioning
confidence: 99%
“…Regarding the impact of management practice, McCombs and Williams (2021) found that in an epidemic situation, shorter-term performance expectations do not impair employees' wellbeing. However, this can only be achieved if management communication inspires trust, is caring and sufficiently detailed in terms of tasks (Shipman et al, 2021).…”
Section: Organizational Citizenship Behavior and Remote Workmentioning
confidence: 99%
“…The leadership style adopted by the surveyed managers can primarily be categorized as being that of ‘transformational leadership’ (Conger, 1999; Van Dierendonck et al. , 2014; McCombs and Williams, 2021). Their leadership in crisis events is not about demonstrating a particular personal leadership style but integrating various leadership capabilities within their organizations (“charismatic,” “servant,” “participative” and transactional leadership) (Bowers et al ., 2017; Morse, 2010; Wu et al ., 2021).…”
Section: Discussion Of Results: Leadership Roles Under Crisis As the ...mentioning
confidence: 99%
“…The desire for greater efficiency and competitiveness is the main reason for introducing agile leadership, especially during these challenging times ( Attar and Abdul-Kareem, 2020 ). An agile work environment is characterized by teamwork, a high level of communication, and a low degree of standardization and formalization ( Attar and Abdul-Kareem, 2020 ; McCombs and Williams, 2021 ). It is almost impossible for companies to grow and expand without effective leadership, as is imperative in an ever-changing market ( Bojadziev et al, 2019 ).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…Restrictive measures to curb COVID-19 have led to unexpected job closures worldwide and thus to changed forms of work, and the cessation of economic activity has threatened many jobs ( Lamprinou et al, 2021 ). The pandemic has accelerated the process and forced many companies to be more agile and decentralized and agile leadership is becoming more important ( McCombs and Williams, 2021 ). The benefit of such praxes is shown in the ability to be calm in the face of pressure, open to innovation, and able to keep teams grounded and on the right track ( Attar and Abdul-Kareem, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation